2008
DOI: 10.1097/cad.0b013e3282f2c0bc
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study of chemoimmunotherapy in the treatment of metastatic melanoma

Abstract: Combining chemotherapy and immunotherapeutic agents such as interleukin-2 and interferon alpha-2b might improve treatment results in metastatic melanoma (MM) patients compared with chemotherapy alone. This prospective study evaluated the potential efficacy of a biochemotherapy regimen followed by maintenance biotherapy for the treatment of MM. Twenty-two patients with stage IV melanoma were treated for 5 consecutive days with cisplatin at 20 mg/m, vinblastine at 1.6 mg/m, and dacarbazine at 160 mg/m. Pegylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Metastatic malignant melanoma remains an incurable disease in many patients, and the 5-y survival rate for stage IV melanoma is still 15%-20% (9). A few years ago, specific tumor geno-and phenotypes were identified that present higher response rates to various targeted treatments, such as the BRAF mutation V600E to treatment with the tyrosine kinase inhibitor vemurafenib, NY-ESO-1 expression and immunotreatment with Ipilimumab (BristolMyers Squibb), or c-kit mutation to Imatinib (Novartis).…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic malignant melanoma remains an incurable disease in many patients, and the 5-y survival rate for stage IV melanoma is still 15%-20% (9). A few years ago, specific tumor geno-and phenotypes were identified that present higher response rates to various targeted treatments, such as the BRAF mutation V600E to treatment with the tyrosine kinase inhibitor vemurafenib, NY-ESO-1 expression and immunotreatment with Ipilimumab (BristolMyers Squibb), or c-kit mutation to Imatinib (Novartis).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is believed to be the most effective treatment for melanoma, and an adjuvant multimodal therapy might be beneficial, especially in patients with metastasis 60 . A good clinical course has also been obtained by immunotherapy with interferon 61 . The 5‐year overall survival rate of patients with primary oral melanoma is 15%, with a median survival of 25 months 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Median progression-free survival was 2.5 months, and toxicities were primarily hematological, including one treatment-related bleeding complication leading to death. A smaller study of 22 metastatic melanoma patients receiving a regimen of CVD with PEG-IFN-2b, subcutaneous IL-2 and oral 13-cis-retinoic acid, with maintenance biotherapy for those with clinical response after six courses, www.intechopen.com provided 12 objective responses with seven maintenance-receiving patients having stable disease after six months (Recchia et al, 2008). Median progression-free and overall survivals were 23.3 and 45.7 months, respectively, with mostly hematological toxicities and 21% of patients exhibiting grade 2 autoimmune reactions.…”
Section: Cytokines and Chemotherapymentioning
confidence: 99%